Shared services: case study on the performance of the controllership in 13 Latin American countries - Ana Cristina de Faria; Márcio Antonio Gonçalves (BBR: Brazilian Business Review)
This paper aimed to evaluate whether the implantation of Shared Services (SS) of Controllership, as an area which generates management accounting information suitable for managers in 13 Latin American Countries to make decisions, satisfactorily contributes to the management process of the organization globally. A case study was carried out involving 22 managers and 9 controllers. The results shows that SS attempt to join, in the same place, support processes of the business units of the corporation so that the company¿s strategic aspects can be focused on to eliminate functions and duplicated activities. The limitation was the study of only a multinational organization, but it was found that SS contribute to the decision-making process of managers, because they operate with high level services, stimulate technological investments, generate economies of scale and obtain the satisfaction of its internal customer-partners. SS can function as an independent unit, with their own structure and resources, control of the executed activities, sharing useful and convenient services with other areas in a single company, in any segment and even globally.